Penyebab Amal Ibadah di Tolak - Martoyo Martoyo; Putri Pebrinawati (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Abstract: Religion is an inseparable reality in life, both individual and collective. Religion is considered as a way of life for humans to guide humans so that their lives are not chaotic, religion serves to maintain human integrity in fostering relationships with God and relationships with fellow humans and with the nature that surrounds them (Kahmad, 2000).